2022
DOI: 10.1021/acs.jnatprod.1c01078
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 8-Fluoroneocryptolepine and Evaluation for Cytotoxic Activity against AGS Cancer Cells

Abstract: Neocryptolepine derivatives have attracted great interest because of their unique cytotoxic activity. 8-Fluoroneocryptolepine (8FNC) was synthesized, and its cytotoxicity was evaluated by MTT assay in AGS gastric cancer cells and gastric mucosa GES-1 cells. 8-Fluoroneocryptolepine showed greater selectivity and cytotoxicity to AGS cells than the cisplatin (CIS) and fluorouracil (5-Fu) commonly used in clinical treatment of gastric cancer. Most importantly, we significantly improved the cytotoxic effect of 8FNC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…As is shown in Figure 4 , untreated cells showed that the nuclei were similar in size, and uniformly and lightly stained. Nevertheless, AGS cells treated with CCS2 at different concentrations showed typical morphological changes ( Ma et al, 2022 ), such as chromatin condensation, densely stained nuclei, and apoptotic bodies. These results suggested that apoptosis could be the potent mechanism of anti-proliferative activity.…”
Section: Resultsmentioning
confidence: 99%
“…As is shown in Figure 4 , untreated cells showed that the nuclei were similar in size, and uniformly and lightly stained. Nevertheless, AGS cells treated with CCS2 at different concentrations showed typical morphological changes ( Ma et al, 2022 ), such as chromatin condensation, densely stained nuclei, and apoptotic bodies. These results suggested that apoptosis could be the potent mechanism of anti-proliferative activity.…”
Section: Resultsmentioning
confidence: 99%
“…MGC-803, AGS, and HeLa cell lines were also purchased from the Institute of Basic Medical Sciences, Chinese Academy of Medical Sciences (Beijing, China). The cytotoxicities of the isolates were evaluated using a modified MTT assay [63]. AGS and HeLa cells were cultured in RPMI 1640 medium, while MGC-803 cells were cultured in DMEM, supplemented with 10% FBS.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…Apoptosis, which occurs normally during development and aging, is a homeostatic mechanism for maintaining tissue cell populations and an important strategy for treating cancer [27]. Apoptosis leads to cell death with cell nuclear pyknosis and apoptotic body production, which was observed via fluorescence microscopy after Hoechst 33258 staining [27,28]. As shown in Figure 5A, untreated cells showed uniform blue fluorescence, but Hela cells treated with 1 for 48 h showed clear apoptotic signals, with shrinkage of chromatin, fragmentation of nuclei, and bright blue fluorescence, and apoptotic bodies appeared in apoptotic cells.…”
Section: Compound 1 Could Cause Apoptosis Of Hela Cellmentioning
confidence: 99%
“…When the cells were walled and incubated for 48 h with different concentrations of the drug. The culture solution was aspirated and incubated with JC-1 staining solution for 20 min at 37 • C [28]. The supernatant was then aspirated and washed twice with JC-1 staining buffer before being observed under a fluorescence microscope and photographed.…”
Section: Mitochondrial Membrane Assaymentioning
confidence: 99%
See 1 more Smart Citation